ON THE CLASSIFICATION OF THE MEZO-CENOZOIC SECRETING BENTHIC FORAMINIFERA - Bugrova E.M. (My University, 2002)
The state of the classification of benthic secreting Foraminifera is reviewed. The classification, which ranks the Foraminifera as a class, is modified using the criteria of Fursenko's systematics (morphological, ontogenetic, ecological, and geochronological). The role of these criteria are illustrated by examples.
Keywords: Cenozoic; Mesozoic; Cenozoic; Кайнозой; Мезозой; Mesozoic